UNRAVELING THE EFFECTS OF TRANSFER PRICING DOCUMENTATION REGULATION: INDONESIA’ EVIDENCE - Dwi Saputra, Anggari (UI Scholars Hub, 2023)
To counter tax avoidance using transfer mispricing practices, Indonesia introduced a transfer pricing documentation policy. This policy requires taxpayers to be transparent with their transfer pricing decisions. Treating the implementation of this policy as a shock to the taxpayers, this paper examines how the transfer pricing documentation policy affects a firm's tax avoidance behaviour by employing regression discontinuity design and difference-in-difference. Immediately after introducing the policy, a regression discontinuity analysis results indicate a 0.9 percentage point increase in tax/sales among taxpayers obligated to prepare transfer pricing documentation. A 0.3 to 0.7 percentage point increase in the tax/sales of the treatment group is observed when difference-in-difference is established. These findings show that such policy implementation can discourage taxpayers' tax avoidance behaviour. In light of these results, the Indonesian tax authority may consider taking several actions to improve the implementation of TP docs, such as amending summary of TP docs so that it contains more valuable information regarding taxpayer’s arm’s length principle application, requiring simple TP docs for taxpayers below the threshold, providing continuously providing assistance and capacity building to the taxpayers regarding appropriate TP docs preparation and arm’s length principle application.